Rights and responsibilities - Sloan, Stephen (McGraw-Hill ESL/EST, 2004)
Rights and Responsibilities: Reading and Communication for Civics will greatly aid newcomers to the United States who must simultaneously learn English and adjust to American housing, work, school, finance, health, and political systems and practices